Efficacy of selected insecticide against aphid (Myzus persicae) on long bean (Vigna sesquipedalis) / Nurulamirah Mohmad Khir - Mohmad Khir, Nurulamirah (Faculty of Plantation and Agrotechnology, 2015)
A field experiment was conducted at the share farm of Universiti Teknologi MARA Jasin, Me1aka, Malaysia during January to Apri12015 to know the efficacy of selected insecticide and determine the insecticide that reduce quickly the number of aphid (Myzus persicae) population on long bean (Vigna sesquipedalis). Observation on number of aphid were taken on one day before treatment, one day, 3 days, 7 days and 14 days after treatment sprayed. Insecticide of Confidor showed significantly to reduce quickly on number of aphid population as compared to insecticide of Mospi1an on long bean. The resulted of experiment was showed Confidor treated plant more efficacy of selected insecticide against aphid on long bean rather than Mospilan treated plant.